Swiss Canine Cancer Registry 1955–2008: Occurrence of the Most Common Tumour Diagnoses and Influence of Age, Breed, Body Size, Sex and Neutering Status on Tumour Development. Issue 2 (August 2016) - Grüntzig, K.; Graf, R.; Boo, G.; Guscetti, F.; Hässig, M.; Axhausen, K.W.; Fabrikant, S.; Welle, M.; Meier, D.; Folkers, G.; Pospischil, A.
Summary: This study is based on the Swiss Canine Cancer Registry, comprising 121, 963 diagnostic records of dogs compiled between 1955 and 2008, in which 63, 214 (51.83%) animals were diagnosed with tumour lesions through microscopical investigation. Adenoma/adenocarcinoma ( n = 12, 293, 18.09%) was the most frequent tumour diagnosis. Other common tumour diagnoses were: mast cell tumour ( n = 4, 415, 6.50%), lymphoma ( n = 2, 955, 4.35%), melanocytic tumours ( n = 2, 466, 3.63%), fibroma/fibrosarcoma ( n = 2, 309, 3.40%), haemangioma/haemangiosarcoma ( n = 1, 904, 2.80%), squamous cell carcinoma ( n = 1, 324, 1.95%) and osteoma/osteosarcoma ( n = 842, 1.24%). The relative occurrence over time and the most common body locations of those tumour diagnoses are presented. Analyses of the influence of age, breed, body size, sex and neutering status on tumour development were carried out using multiple logistic regression. In certain breeds/breed categories the odds ratios (ORs) for particular tumours were outstandingly high: the boxer had higher ORs for mast cell tumour and haemangioma/haemangiosarcoma, as did the shepherd group for haemangioma/haemangiosarcoma, the schnauzer for squamous cell carcinoma and the rottweiler for osteoma/osteosarcoma. In small dogs, the risk of developing mammary tumours was three times higher than in large dogs. However, small dogs were less likely to be affected by many other tumour types (e.g. tumours of the skeletal system). Examination of the influence of sex and neutering status on tumour prevalence showed that the results depend on the examination method. In all sampling groups the risk for female dogs of developing adenoma/adenocarcinoma was higher than for male dogs. Females had a lower risk of developing haemangioma/haemangiosarcoma and squamous cell carcinoma than males. Neutered animals were at higher risk of developing specific tumours outside the genital organs than intact animals. The sample size allows detailed insight into the influences of age, breed, body size, sex and neutering status on canine tumour development. In many cases, the analysis confirms the findings of other authors. In some cases, the results are unique or contradict other studies, implying that further investigations are necessary.